The Association Between Tax Aggressiveness, Sustainability Disclosure and Cost of Equity - Amrie Firmansyah; Novelyn Debora Sinaga (AFEBI Management and Business Review, 2022)
Companies that have a high cost of capital show high risk. Investors expect a higher rate of return to compensate for the investors they will bear. This study examines whether sustainability disclosure and tax aggressiveness affect the equity cost. The research data were obtained from company financial statements, annual reports, and sustainability reports of non-financial sector companies listed in the 50 companies with market capitalization from 2017 to 2020. Data sourced from www.idx.co.id, www.idnfinancial.com and the company's official website. Based on purposive sampling, the total sample used in this study amounted to 108 observations. Hypothesis testing is conducted by using multiple linear regression analysis for panel data. The results suggest that the disclosure of sustainability is negatively associated with the cost of equity, while tax aggressiveness is positively associated with the cost of equity. This research indicates that the Indonesia Financial Services Authority needs to increase supervision over the implementation of sustainability carried out by listed companies.